Comparing transformational and instrumental leadership: The influence of different leadership styles on individual employee and financial performance in Brazilian startups - Cristiane Benedetti Chammas; José Mauro da Costa Hernandez (Innovation & Management Review, 2019)
Purpose - The purpose of this study is to investigate the influence of transformational and instrumental leadership on the individual performance of the employee and the financial performance in Brazilian startups. Design/methodology/approach - The adopted methodological construction strategy was structural equation modeling, with the purpose of applying the model to primary data collected from a sample of leaders of Brazilian startups (n = 126). Findings - Results suggest that when leadership types are analyzed separately, both directly influence employee performance. Originality/value - This study has four main contributions: to test the influence of the two leadership styles on employee performance and thus to help advance the theoretical understanding of leadership; to perform this test in the context of Brazilian startups; to equip professionals with more information about the effects of crucial leadership types on individual type of employee performance; and to expand knowledge for recruitment and managerial training in initial-stage companies.
Keywords: 650; Performance; Transformational leadership; Instrumental leadership; Startups